THE IMPACT OF COVID-19 ON STUDENTS’ WILLINGNESS TO COMMUNICATE IN ENGLISH IN HIGHER EDUCATION INSTITUTIONS IN A DIGITAL CONTEXT (HEIs) - Anna Lynn Abu Bakar; Irma Wani Othman; Saifulazry Mokhtar; Sohaimi Mohd Esa, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The outbreak of the Covid-19 Pandemic has brought a shift in the way the teaching and learning process has been conducted in the education field. Most of the lessons are conducted in a digital context for the safety of both teachers and students. Thus, this study aims to look into the impact of the pandemic on students’ willingness to communicate (WTC) in English in a digital context in a local higher education institution (HEIs) in Sabah, Malaysia. A qualitative approach was employed in this study involving 25 pre-university students. The data was obtained from a focus group interview and was later transcribed and coded into dominant and sub-dominant themes. The findings revealed that the students unanimously agreed that having classes in a digital context does affect their WTC in English. It is hoped that these findings would give a better insight to English language instructors (ELIs) to plan a conducive learning environment that could facilitate students' WTC in a digital context.